The concept of “wisdom” in a Russian fairy tale - Xiaoyan Huo (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ., 2023)
The description of the concepts of the Russian language is impossible without referring to folklore, since it is in this linguocultural layer that it is possible to identify the sources and ways of the formation of the mental characteristics of the Russian people. The concept "Wisdom" is one of the central concepts of the Russian folklore picture of the world. It is extremely widely represented in the genre of folk fairy tales. Usually women in fairy tales are wiser than men.